HANDS ON TRAINING FOR PRE-ANALYTIC SAMPLE OF HISTOPATHOLOGY AND CYTOLOGY EXAMINATION IN JAMBI CITY - Quzwain, Fairuz Chatib; Dewi, Hasna; Lipinwati; Hanina; Miftahurrahma (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
The pre-analytic stage is an important stage in the anatomical pathology examination. in the specimen are prepared by the assistant nurse surgeon or clinician or laboratory analyst who receives the cytology sample, so it is necessary to provide correct and appropriate information for them and training in handling these samples is carried out. This activity is carried out to improve the understanding of health workers in managing samples and tissues at the pre-analytical stage. In this training, a standard operating procedure (SOP) for pre-analytical handling of histopathology and cytology samples will also be prepared, which is expected to be recognized by the association as an SOP for its members that applies in Jambi province. The method implemented is direct training on tissue and fluid samples and evaluation is carried out by assessing the pre-test and post-test after the activity is carried out. The results of the activity assessment showed a significant increase in the understanding and knowledge of the participants in the activity by looking at the increase in the pre-test and post-test scores. There is an increase in the understanding and knowledge of the training participants regarding the management of tissue and fluid samples at the pre-analytical stage.